UTILIZATION OF BANANA PEELS IN SEVERAL INDUSTRY: AN OVERVIEW - Disha Paul,; Souvik Tewari, (The Bioscan, 2024)
The banana, botanically known as Musa spp. is one of the most widely grown and consumed fruits, producing a significant amount of trash each year in the form of peels. Due to lack of awareness and knowledge regarding beneficial effects of banana peels, people typically waste banana peel. Numerous bioactive substances, including phytosterol, polyphenols, carotenoids, and biogenic amines are abundant in banana peels. In addition, it has good amounts of dietary fibre and minerals like iron, calcium, sodium, phosphorus, and magnesium. There are several sectors that use banana peels are: Food processing, Medicine industry, Beverage industry, and also agriculture industry. This review article mainly summarized or focused on the nutritional characteristics, bioactive elements and potential health-promoting properties of banana peels and its utilization in several business sector such as Food and beverages industry, Nutraceutical and medicinal industry or so on.